Determining post-operative morbidity and mortality following gynecological oncology surgery: protocol for a multicenter, international, prospective cohort study (Global Gynaecological Oncology Surgical Outcomes Collaborative-GO SOAR) - Gaba, Faiza; Bizzarri, Nicolò; Kamfwa, Paul; Saiz, Allison; Blyuss, Oleg; Paranjothy, Shantini; Ramirez, Pedro T; Cibula, David (International journal of gynecological cancer, 2021)
BACKGROUND: The Global Gynaecological Oncology Surgical Outcomes Collaborative (GO SOAR) aims to develop a network of gynecological oncology surgeons, surgical departments, and other interested parties that will have the long-term ability to collaborate on outcome studies. The protocol for the first collaborative study is presented here. PRIMARY OBJECTIVE: To evaluate international variation in 30-day post-operative morbidity and mortality following gynecological oncology surgery between very high/high and medium/low human development index country settings. HYPOTHESIS: There is no variation in post-operative morbidity and mortality following gynecological oncology surgery between very high/high and medium/low human development index country settings. STUDY DESIGN: International, multicenter, prospective cohort study. Patient data will be collected over a consecutive 30-day period through gynecological oncology multidisciplinary teams/tumor boards and clinics across different human development index country groups. All data are collected on a customized, secure, password protected, central REDCap database. MAJOR INCLUSION/EXCLUSION CRITERIA: Inclusion criteria include women aged ≥18 years undergoing elective/emergency, curative/palliative surgery for primary/recurrent tubo-ovarian/peritoneal, endometrial, cervical, vulval, vaginal, gestational trophoblastic malignancies. Surgical modality may be open, minimal access (laparoscopic/robotic), or vaginal. PRIMARY ENDPOINT: 30-day post-operative morbidity and mortality defined as per Clavien-Dindo classification system. SAMPLE SIZE: 1100 (550/arm). ESTIMATED DATES FOR COMPLETING ACCRUAL AND PRESENTING RESULTS: It is estimated recruitment will be completed by 2022 and results published by 2023. TRIAL REGISTRATION: ClinicalTrials.gov registry: NCT04579861 (https://clinicaltrials.gov/ct2/show/NCT04579861).
Keywords: výsledek terapie; morbidita; Gynecologic Surgical Procedures; ženské pohlaví; Treatment Outcome; Humans; prospektivní studie; Prospective Studies; Female; nádory ženských pohlavních orgánů; Morbidity; kohortové studie; gynekologické chirurgické výkony; Genital Neoplasms, Female; lidé; Cohort Studies